A construção da docência em música no estágio supervisionado: um estudo na UFSM - Buchmann, Letícia Taís (2008)
This thesis was carried out following the research line Education and Arts of the Postgraduate Education Program at the Federal University of Santa Maria (UFSM), Brazil, and it is one of the works originated in the research group FAPEM (Qualification, Action and Research in Musical Education), registered at the Brazilian research support agency CNPq. This work aims at investigating music teaching development in the supervised pre-service teacher training of the Music Course Licentiate s degree at UFSM, from the point of view of a group of six trainees. In order to do so, we sought to understand the trainees conception of training and its relation to primary and secondary education. Besides taking into account the laws related to the theme, our theoretical references included authors from the fields of Education (such as ALARCÃO; TAVARES, 1987; GARCIA, 1999; PIMENTA; LIMA, 2004) and Musical Education (such as MATEIRO, 2002a, 2002b; MATTANA, 2005; BEINEKE; BELLOCHIO, 2007) whose research works focus on teachers professional development and supervised pre-service teacher training. The adopted methodological approach was qualitative, including semi-structured interviews, memory stimulus interviews and video recordings of the trainees classes. Criteria for selecting participants were the trainees interest and availability as well as the researcher s availability for going to the schools at the time the trainees were teaching in order to film them. Data were analyzed following their organization into two categories: (1) conceptions of training, including the supervisor s role, and (2) teaching practice at school, considering that the training was carried out in pairs, its relation to primary and secondary education and the trainees experiences. Based on our interpretation and dialogue with the references concerning teaching development in supervised pre-service teacher training, it was possible to reach some conclusions about music teachers professional development. Thus, we believe this research may contribute relevant data to the teaching profession. We pointed out the sharing of actions by the trainees and their supervisor s mediation, as well as problems and considerations regarding teaching development during training and its relation to music teachers professional development.